Characteristics Predicting a High Caregiver Burden in Patients with Vascular Cognitive Impairment: Using the Apriori Algorithm to Delineate the Caring Scenario - Jhang, Kai-Ming; Wang, Wen-Fu; Chang, Hsin-Fang; Chang, Ming-Che; Wu, Hsin-Hung (Risk management and healthcare policy, 2021)
The aim of this study was to elucidate the factors and caring scenarios associated with a moderate to severe care burden in the caregivers of patients with vascular cognitive impairment (VCI). This cross-sectional study included 158 patients with VCI and their caregivers who were managed by the dementia collaborative care team at Changhua Christian Hospital, Taiwan. Gender, age, clinical dementia rating, walking ability, behavioral symptoms, and psychological symptoms were the variables from the patients with VCI. Age, marital status, relation to the VCI patient, education, employment status, help of key activities, type of primary care, frequency of care, ZBI (Zarit burden interview) caregiving burden, and caregiver's mood were the evaluated variables for the caregivers. The Apriori algorithm was used to identify the attributes that resulted in different caregiving burdens from a comprehensive viewpoint of both VCI patients and their caregivers. A total of 1193 rules were identified with 1134 rules belonging to caregivers with a mild to moderate burden and 59 rules belonging to caregivers with a moderate to severe burden. Seven general rules were created based on a summary of these 59 rules. The results showed that an employed female caregiver who was taking care of her husband alone for ≥6 days per week, and who was helping with all key activities was likely to experience a moderate to severe burden when the patient had VCI. Moreover, if the caregiver had a relatively low education level and expressed an abnormal mood during the assessment, this increased the likelihood of the caregiver having a moderate to severe burden. The caregiver's gender, relation to the care recipient, education level, mood status, employment status, and care loading were associated with a higher burden of care for caregivers of patients with VCI. Therefore, a dementia care team should provide personalized training for caregivers about the disease, care skills for specific behaviors and psychological symptoms of dementia (BPSD), and strategies to cope with their own feelings. Caregivers should also be referred to appropriate social resources, such as support groups or respite care.